Spiritual Care Perspectives of Elderly Individuals with Parkinson's Disease and Formal Caregivers: A Qualitative Study in Turkish Nursing Homes - Kurtgöz, Aslı (Journal of religion and health, 2024)
This study aimed to determine the perceptions and experiences of elderly individuals with Parkinson's disease and formal caregivers regarding spiritual care. A qualitative study was conducted using a descriptive phenomenological design. Fifteen formal caregivers and eight elderly individuals with Parkinson's disease from two nursing homes in Türkiye participated in the study. Data were collected through face-to-face individual interviews, and thematic analysis was employed to examine the data. Two themes were obtained from the data analysis: (I) spiritual care in nursing homes and (II) living with Parkinson's disease in nursing homes. Findings showed that living in a nursing home with Parkinson's disease affects the spiritual dimensions of elderly individuals and increases their spiritual needs. Additionally, it was found that although formal caregivers implemented a diverse range of practices to address the spiritual care needs of individuals residing in a nursing home, they did not offer any specific spiritual care practices for individuals with Parkinson's disease. Based on our findings, it is considered necessary to have spiritual counselors and formal caregivers with expertise in Parkinson's disease in nursing homes.